Naturally processed HLA class II peptides reveal highly conserved immunogenic flanking region sequence preferences that reflect antigen processing rather than peptide-MHC interactions. - Godkin, A; Smith, K; Willis, A; Tejada-Simon, M; Zhang, J; Elliott, T; Hill, A (2001)
MHC class II heterodimers bind peptides 12-20 aa in length. The peptide flanking residues (PFRs) of these ligands extend from a central binding core consisting of nine amino acids. Increasing evidence suggests that the PFRs can alter the immunogenicity of T cell epitopes. We have previously noted that eluted peptide pool sequence data derived from an MHC class II Ag reflect patterns of enrichment not only in the core binding region but also in the PFRS: We sought to distinguish whether these enrichments reflect cellular processes or direct MHC-peptide interactions. Using the multiple sclerosis-associated allele HLA-DR2, pool sequence data from naturally processed ligands were compared with the patterns of enrichment obtained by binding semicombinatorial peptide libraries to empty HLA-DR2 molecules. Naturally processed ligands revealed patterns of enrichment reflecting both the binding motif of HLA-DR2 (position (P)1, aliphatic; P4, bulky hydrophobic; and P6, polar) as well as the nonbound flanking regions, including acidic residues at the N terminus and basic residues at the C terminus. These PFR enrichments were independent of MHC-peptide interactions. Further studies revealed similar patterns in nine other HLA alleles, with the C-terminal basic residues being as highly conserved as the previously described N-terminal prolines of MHC class II ligands. There is evidence that addition of C-terminal basic PFRs to known peptide epitopes is able to enhance both processing as well as T cell activation. Recognition of these allele-transcending patterns in the PFRs may prove useful in epitope identification and vaccine design.